PENGEMBANGAN MODEL HEWAN PERCOBAAN TIKUS DIABETES MELLITUS TIPE 2 KARENA RESISTENSI INSULIN YANG DIINDUKSI DENGAN HUMAN INSULIN JANGKA PANJANG - Yance Anas; Ria Rositasati; Meita Rafika Fitriani; Suharjono Suharjono (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACT Hyperinsulinemia may precede insulin resistance in patients with Type 2 diabetes. In this study, we tried to reveal an influence of long-term treatment of human insulin to hyperglycemic and insulin resistance in male Wistar rats. Before the experiment, blood-glucose levels measured two hours after 2 g/Kg glucose imposition. Rats receive human insulin (0.45-1.80) IU/KgBW/day subcutaneously every day for 14 days. Furthermore, human insulin 1.8 IU/KgBW/day also provide a period of7,14and 21days. At theend of the experiment,we mademeasurements ofblood-glucoselevelstwo hoursafterthe imposition glucose.There are, the influence oflong-termtreatment of human insulin determined bycomparing the blood-glucoselevelsbeforeandafter insulin treatment. Insulin resistance isdeterminedby comparing thehypoglycemiceffect of glibenclamide 10 mg/Kg BW to the control group. The results concluded that the humaninsulin1.80 IU/KgBW/day treatment for 14dayscan improveblood-glucoselevel'sWistarmale ratsup to126.369mg/dL(p<0.05)withpatternsdoes notdepend onthe length of timeof administration.The averageof % hypoglycemiceffect of glibenclamide10mg/kgBW in ratswhoreceived treatment with human insulin 1.80IU/kg BW/dayswereat 18,31%,smaller thancontrols (62.20%) (p<0.05). Decrease in hypoglycemic effects of glibenclamide 10 mg/kg BW caused by mice has insulin resistance might be due to a result of long-term insulin administration. Keywords : Human insulin, insulin resistance, Type 2 diabetes animal models